Laboratory and Field Observations for Golden Horn Marine Clay - Kilic, Havvanur; Berilgen, Saadet Arzu; Bicer, Perihan; Yildirim, Mustafa (TAYLOR & FRANCIS INC, 2010)
Istanbul, the largest city in Turkey and one of the major metropolitan areas in the world, cleaned one of its environmentally polluted areasGolden Hornby dredging 5 million m3 of the bottom sediments and pumping the resulting sludge to a storage area behind a dam built at an abandoned rock quarry site in Alibey district. The reclamation of the land that formed over the storage area of Golden Horn dredged material is socially and economically very desirable. In this paper, results from experimental studies that are focused on determining the shear strength behavior of the dredge material and undisturbed soil are presented. Slurry consolidometer test, large model tests and small model tests are used to consolidate the dredged soil samples from Halic to simulate the natural consolidation behavior of these soils. Shear strength parameters are determined by laboratory vane tests; unconfined compression tests; undrained-unconsolidated (UU) and consolidated-undrained (CU) triaxial tests on samples that are obtained through in situ undisturbed samples and laboratory model tank and slurry consolidation. Moreover, the effects of fly ash and lime additives on the undrained shear strength were determined by mixing the materials with the dredged clay from Golden Horn during the model experiments conducted in the laboratory. Based on these findings, equations are proposed that govern the relationships between undrained shear strength and water content value.
Keywords: field and laboratory vane test; marine clay; soil improvement; undrained shear strength; CONSOLIDATION; Engineering; Oceanography; Mining & Mineral Processing